Self‐dilatation of benign oesophageal strictures: a literature review. Issue 7 (6th May 2021) - Alwan, Mostafa; Giddings, Charles E.
Abstract: Background: Benign oesophageal strictures can have several aetiologies and often require serial endoscopic dilatation. The aim of this study was to review the existing literature regarding the efficacy of self‐dilatation for benign oesophageal strictures. Methods: This study presents the results of a systematic review that was performed on the available literature using Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. Full‐text articles from Medline, PubMed and Embase were used, as well as associated reference lists. This study systematically reviews the literature to present the efficacy and different outcome measurements associated with self‐dilatation of benign oesophageal strictures. Results: This study identified 13 articles with 274 participants. Conclusion: Self‐dilatation for refractory benign oesophageal strictures is effective regardless of aetiology. It is well tolerated, safe and leads to lasting symptom resolution in the majority of patients. Abstract : We review 13 articles with 274 patients to study the efficacy of self‐dilatation in benign oesophageal strictures. The review suggests that self‐dilatation is a safe and effective management option.